INTERNAL FACTORS OF ENGLISH LEARNING ACHIEVEMENT - Pertiwi, Desy Leistyaning; ., Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to describe the degree of internal factors (age, motivation, anxiety, personality, and strategy) which may influence English learning achievement of Year-10 students at SMA Taman Mulia Kubu Raya. There were 20 participants in this research. This research used Likert Scale to analyze the data. The research finding showed that (1) strategy is dominant internal factor of English learning achievement. The percentage of strategy is the high achievers 80.00% and the low achievers 60.63% . (2) Students with high achievement (69.31%) are more anxious than the students with low achievement (61.87%). (3) The students with high achievement (67.90%) have more motivation than the students with low achievement (64.96%). (4) Students with high achievement (52.92%) have higher percentage of personality than the students with low achievement (50.00%). (5) Age is not really influence students English achievement. Students with more positive internal factors would have a better English learning achievement.   Keywords: Internal factors, English Learning Achievement   Abstrak: Penelitian ini bertujuan untuk menggambarkan tingkat faktor internal (usia, motivasi, kecemasan, kepribadian, dan strategi) yang dapat mempengaruhi prestasi belajar bahasa Inggris siswa kelas 10 SMA Taman Mulia Kubu Raya. Ada 20 partisipan dalam penelitian ini. Penelitian ini menggunakan skala Likert untuk menganalisa data. Hasil penelitian menunjukkan bahwa (1) strategy adalah faktor internal yang dominan dalam prestasi belajar bahasa inggris. Persentase strategi adalah siswa berprestasi tinggi 80,00% dan siswa berprestasi rendah 60,63%. (2) Siswa dengan prestasi tinggi (69,31%) lebih cemas dibandingkan siswa dengan prestasi rendah (61,87%). (3) Siswa dengan prestasi tinggi (67,90%) memiliki motivasi yang lebih dibandingkan siswa dengan prestasi rendah (64,96%). (4) Siswa dengan prestasi tinggi (52,92%) memiliki persentase kepribadian yang lebih tinggi dibandingkan siswa dengan prestasi rendah (50,00%). Usia tidak terlalu mempengaruhi prestasi belajar bahasa Inggris siswa. Siswa dengan faktor internal positif yang lebih akan memperoleh prestasi belajar bahasa Inggris yang lebih baik. Kata kunci: Faktor Internal, Prestasi Belajar Bahasa Inggris